The Welfare Multiplier of Public Infrastructure Investment - Ganelli, Giovanni (IMF Working Papers; Working Paper ;, 2016)
We analyze the welfare multipliers of public spending (the consumption equivalent change in welfare for one dollar change in public spending) in a DSGE model. The welfare multipliers of public infrastructure investment are positive if infrastructure is sufficiently effective. When the medium-term output multipliers are consistent with the empirical estimates (1-1.4), the welfare multiplier is 0.8. That is, a dollar spent by the government for investment raises domestic welfare by equivalent of 0.8 dollars of private consumption. This suggests that the welfare gains of public infrastructure investment, if chosen wisely, may be substantial.